Survival and quality of life in breast cancer patients - Vahdani Nia MS; Sadighi J; Montazeri A (Payesh, 2005)
Objective(s): To study the contribution of quality of life in relation to survival in breast cancer patients. Methods: In all, 128 breast cancer patients were followed up for 5 years. At 5 years 79 patients were alive and 49 patients were dead, given an overall survival rate of 62%. Quality of life was measured using the EORTC QLQ-C30 and its breast cancer questionnaire (QLQ-BR23) after completion of the initial treatment. Results: Data for 116 patients were available for analysis. 44 patients presented with metastatic disease and 95 cases underwent mastectomy. Using the Cox regression model and adjusting for age at diagnosis and disease stage, we found that receiving neo-adjuvant therapy as initial treatment and low global quality of life were independent predictors of poorer survival (Hazard ratio for neo-adjuvant therapy=12.4, 95% CI=4.9 to 31.0, P<0.0001; And hazard ratio for global quality of life=0.98, 95% CI=0.97 to 0.99, P=0.007). Conclusion: These findings indicate that the initial treatment and overall quality of life are important predictors of survival in breast cancer patients. This suggests that using standard management guidelines and improving quality of life might improve survival in breast cancer patients.